Comparison of leg length discrepancy after total hip arthroplasty: Direct anterior and posterior lateral approach. - Yang Lu; Xiang Li; Yihe Hu; Fengchao Zhao (PLoS ONE)
Background Leg length discrepancy (LLD) after total hip arthroplasty (THA) is a clinical entity that deteriorates clinical outcomes and patients' satisfaction. Few articles have compared LLD after THA by different surgical approaches. Methods A total of 358 consecutive patients who underwent primary THA between January 2016 and November 2018 were retrospectively reviewed. All 4 surgeons performed THA through both direct anterior approach (DAA) and posterior lateral approach (PLA). The primary outcome measurement was LLD. LLD was measured on post-operative anteroposterior bilateral hip radiograph. The secondary outcomes were acetabular abduction, acetabular anteversion, perceived LLD (pLLD) and HHS at 6 weeks, 1 year and 5 years. Intergroup analyses were performed using the Chi-square test for enumeration data and the independent sample t-test for quantitative data. Results There was no inter-group difference in terms of patients' demographics. The DAA group had decreased LLD compared to the PLA group (3.0 ± 5.9mm vs. 4.2 ± 4.5mm, p = 0.027). Meanwhile, the DAA group had a smaller acetabular anteversion than the PLA group (12.9 ± 2.9 vs. 18.4 ± 2.9, p < 0.01). At 6-week follow-up, the DAA group had higher HHS (82.2 + 6.2 vs. 80.5 + 6.6, p = 0.015) and less pLLD (P = 0.001) compared to the PLA group. Conclusions DAA results in more accurate leg length equalization, reduced pLLD, and improved short-term outcomes compared with PLA.